The Efficacy of Housekeeping Simulation to the Performance of Hospitality Management Students in Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The housekeeping department is an essential part of the hotel industry, as is the hospitalitymanagement curriculum. Different trainings and seminars were also conducted to enhancethe knowledge and skills of the students. Thus, this study aims to determine the efficacy ofhousekeeping simulations on the performance of BSHM students at Bestlink College of thePhilippines.The study revealed that having a housekeeping simulation is strongly effective in those BSHMstudents' performance; the impact of housekeeping practices may boost the students' skills.However, some of the respondents encountered different challenges while performinghousekeeping simulation.Based on the findings and data gathered, the researchers construct guidelines to improve theperformance of BSHM students towards housekeeping simulations.
Keywords: Business